Across the universe [videorecording (Blu-Ray)] - Clement, Dick; La Frenais, Ian; Wood, Evan Rachel, 1987-; Sturgess, Jim; Anderson, Joe, 1982-; Fuchs, Dana, 1978-; Luther, Martin (Singer); Carpio, T. V. (Teresa Victoria), 1981-; Delbonnel, Bruno; Lennon, John, 1940-1980; McCartney, Paul; Harrison, George, 1943-2001; et al. (Sony Pictures Home Entertainment, 2008)
In the 1960s, against the backdrop of The Beatles' music and the Vietnam War, Jude, a struggling artist and dockworker from Liverpool, embarks on a journey to the United States in search of his long-lost father. There, he encounters Lucy, a sheltered American girl, and their love story unfolds. As they navigate their relationship, they are drawn into the world of peace activism when Lucy's brother, Max, is drafted to fight in the Vietnam War. Together, they confront the challenges of their different backgrounds and become entangled in a tale of romance, music, and the fight for peace.